The Effect of Problem-Based Learning Instructional Units on Acquiring the Kip-Up Skill on the Horizontal Bar - Ghanim, Maysaa (Journal of Physical Education, 2025)
The research problem emerged from the researcher’s observation that many students encounter difficulties in learning certain curricular skills in gymnastics, particularly the kip-up skill on the horizontal bar, which is considered challenging due to the lack of understanding of the correct technique and the inability to visualize the appropriate movement pathway for performing the skill. This prompted the researcher to investigate the problem and attempt to provide a solution. The importance of the study lies in designing instructional units based on the problem-based learning approach and examining their effect on acquiring the kip-up skill on the horizontal bar, with the aim of assisting students in mastering this skill through a modern instructional strategy. The researcher employed the experimental method with two groups, experimental and control, as it was suitable for the nature and objectives of the study. The research population consisted of 247 third-year students in the College of Physical Education and Sports Sciences at the University of Diyala during the academic year 2023–2024, from which a sample of 16 students was selected for the experimental group and 16 for the control group. Pre-tests were conducted prior to the intervention. The results indicated that instructional units designed according to the problem-based learning approach are effective in teaching the kip-up skill on the horizontal bar to students at this level, and the researcher recommended adopting such instructional units due to their positive impact on skill acquisition.